Comments on definitions of general local and global Morrey-type spaces - Tararykova, Tamara (Eurasian Mathematical Journal, 2013)
It is proved that in one of the popular definitions of general local and global Morrey-type spaces the functional parameter which enters these definitions can be replaced, without essential loss of generality, by another one, which has better regularity properties.